Analytical performance of centrifuge-based device for clinical chemistry testing - Jamikorn Suk-Anake (2018)
Background: A centrifuge-based device has been introduced to the Samsung Blood Analyzer (SBA). The verification of this analyzer is essential to meet the ISO15189 standard. Methods: Analytical performance was evaluated according to the NCCLS EP05-A method. The results of plasma samples were compared between the SBA and a Hitachi 917 analyzer according to the NCCLS EP09-A2-IR method. Percent recovery was determined via analysis of original control serum and spiked serum. Results: Within-run precision was found to be 0.00-6.61% and 0.96-5.99% in normal- and abnormal-level assays, respectively, while between-run precision was 1.31-9.09% and 0.89-6.92%, respectively. The correlation coefficients (r) were > 0.990. The SBA presented analytical accuracy at 96.64 ± 3.39% to 102.82 ± 2.75% and 98.31 ± 4.04% to 103.61 ± 8.28% recovery, respectively. Conclusions: The results obtained verify that all of the 13 tests performed using the SBA demonstrates good and reliable precision suitable for use in qualified clinical chemistry laboratory service.